Lessons learned from routine, targeted assessment of liquid biopsies for EGFR T790M resistance mutation in patients with EGFR mutant lung cancers. (2nd November 2019) - Mondaca, Sebastian; Offin, Michael; Borsu, Laetitia; Myers, Mackenzie; Josyula, Sowmya; Makhnin, Alex; Shen, Ronglai; Riely, Gregory J.; Rudin, Charles M.; Ladanyi, Marc; Yu, Helena A.; Li, Bob T.; et al.
Abstract: Background: Plasma cfDNA evaluation at acquired resistance to targeted therapies in lung cancer is routine, however, reports of extended clinical application and pitfalls in laboratory practice are still limited. In this study we describe our experience with cfDNA testing using EGFR T790M as a prototype. Methods: Patients with metastatic EGFR -mutant NSCLC patients who underwent plasma EGFR T790M testing at acquired resistance to EGFR tyrosine kinase inhibitors (EGFR-TKI) from January 2016 through August 2017 were identified. Molecular laboratory records were reviewed to assess performance of testing by digital PCR, concordance between plasma and tissue testing, turnaround time (TAT), plasma T790M variant allele frequency (VAF), and its correlations with metastatic sites and clinical outcomes. Results: 177 patients underwent T790M cfDNA testing during this period. Plasma T790M was positive in 32% of patients. The median TAT was shorter for plasma T790M compared to tissue PCR (9 vs. 15 days, p < .0001), and led to osimertinib use in 84% of positive patients. In 52 patients with plasma and tissue T790M evaluation, the concordance was 77%. Plasma T790M VAF did not correlate with time to osimertinib discontinuation ( p = .4). Plasma T790M status correlated with a higher number of metastatic sites (4 vs. 3, p < .001) and bone metastases ( p = .0002). Conclusion: Plasma EGFR T790M testing had shorter TAT compared to tissue testing, however, it was longer than anticipated. Test sensitivity is higher in patients with osseous metastases and with higher metastatic burden suggesting a more limited role for early detection. T790M VAF was not associated with clinical outcomes.